Establishment and application of a rapid assay for GII.4/GII.17 NoV detection based on the combination of CRISPR/Cas13a and isothermal amplification - Li, Jia-Heng; Jing, Duona; Wang, Yu; Xu, Jiayi; Yu, Junxuan; Du, Huisha; Chen, Qing; Tang, Shixing; Zhang, Xu-Fu; Dai, Ying-Chun (Frontiers in Microbiology, 2024)
Norovirus (NoV) is one of the most important agents responsible for viral acute gastroenteritis, among which GII.4 NoV is the predominant strain worldwide and GII.17 NoV surpassed GII.4 in some epidemic seasons. Rapid and accurate gene recognition is essential for a timely response to NoVs outbreaks. In the present study, the highly conserved regions of GII.4 and GII.17 NoVs were identified in the junction of open reading frame (ORF) 1 and ORF2, and then amplified by isothermal recombinase-aided amplification (RAA) followed by the cleavage of CRISPR-Cas13a with screened CRISPR RNAs (crRNA) and RAA primers. The entire detection procedure could be completed within 40 min using a thermostat, and the results could be read out by the naked eye under a portable blue light transilluminator. The assay showed high sensitivity of 97.96% and specificity of 100.0%. It offered a low limit of detection (LOD) of 2.5ｘ10 0 copies/reaction and a coincidence rate of 96.75% in 71 clinical fecal samples. Overall, a rapid and inexpensive detection of GII.4/GII.17 NoVs was established, which makes it possible to be used in areas with limited resources, particularly in low-income countries. And it will contribute to assess transmission risks and implement control measures of GII.4/GII.17 NoVs, making healthcare more accessible worldwide.